Paesaggi d’eccezione, paesaggi del quotidiano. I casi di Cinque Terre, Saint- Émilion, Tokaj - Maristella Storti (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
The project “Exceptional landscapes, daily life landscapes. A comparative analysis of european wine countries of World Heritage”, carried out between 2006 and 2008, has been included in a Research Programme “Landscape and Durable Development” issued by the French Environment Ministry in 2005. The study foresaw the comparative analysis of the local appropriation of the “exceptional universal value” that legitimates the inscription of the “cultural landscapes” of the Cinque Terre, of Saint Émilion and of Tokaj to the World Heritage for Humanity between 1997 and 2002. Three wine countries where the exceptional and daily life are together in different ways and where the idea of conservation and of “mummification” of a certain valuable landscape, must take into account the prerogative of durable development.